Zdravljenje dojenčkov s kisikom v domačem okolju in izkušnje njihovih staršev - Korelc, Marija (Obzornik zdravstvene nege, 2019)
Introduction: Many children with bronchopulmonary dysplasia need prolonged oxygen treatment and some need further treatment with oxygen in the home environment. The purpose of the study was to present parents' experiences related to the preparation for oxygen treatment after a child has been discharged from hospital into a home environment and subsequent support. Methods: A quantitative research approach was used. The measuring instrument was a partially structured questionnaire, based on literature review. The study included 43 parents who took care of their children with oxygen at home from January 2014 to July 2016. Results: The study found that a quarter (25.6%) of parents had difficulties facing that their child had been dismissed from the hospital but needed further oxygen treatment at home. 18.6% of parents had no trouble accepting it. All the interviewed parents gained the majority of information related to oxygen treatment at home and information of technical nature during hospitalization of their child at the Neonatal intensive care unit. The respondents that live in the suburbs reported more mistrust in their own abilities (t = 5.74, p = 0.006) as well as greater fear of the chronical illness their child suffers from (t = 4.82, p = 0.013). On the other hand, the respondents living in the countryside reported less fear.Discussion and conclusion: The study has found that parents are well prepared for the discharge of their child from the hospital, but the situation changes when they are at home and when their child's health condition changes. Good health care education and support is of great importance for the parents' confidence while they are taking care of their children with supplemental oxygen treatement at home.
Keywords: bronchopulmonary dysplasia; brunhopulmonalna displazija; community nurse; domača oskrba; health education; home care; oxygen therapy; patronaža; patronažna medicinska sestra; zdravljenje s kisikom; zdravstvena vzgoja